Peran Kepala Madrasah dalam Peningkatan Mutu Pendidikan - Muharofah Nur Safitri (Program Pascasarjana Universitas Ibrahimy, 2018)
The actor of head Madrasah improved the quality of education is something very urgent, so the head Madrasah must pay more attention to the process of improving the quality of education. By paying attention to the quality of education, the purpose of education will be achieved, so that with the quality of education will facilitate and succeed the learning process and produce output in accordance with the goals of education. The researcher is using methodology of qualitative approach to phenominological perspectives, so that they can understand and appreciate the role of the Aliyah Al-Barokah Madrasah in improving the quality of education. Some of the ways in which heads of madrasah utilize the support for improving the quality of education are placing teachers according to their competence, using facilities, infrastructure appropriately, well, using the budget efficiently, effectively, engaging the community, streamlining communication with committees, the government, safeguarding, and preserving the surrounding environment, maintaining communication with student guardians While overcoming the obstacles by holding internal meetings twice in two months and approaching community leaders and village heads to use the facilities in the padasan village.